SURVEI TOPOGRAFI UNTUK MENENTUKAN GARIS TAMPAK PANDANG BASE TRANSCEIVER STATION (BTS) - Arief Laila Nugraha; Bambang Sudarsono (TEKNIK, 2007)
Base Transceiver Station (BTS) representation one of appliance of supporter of telecommunicationsnetwork. The development of BTS have to each other in circuit by other BTS or which have been planned.The situation BTS in circuit between other BTS without obstacle are called Line of Sight (LoS). Thetopographic survey is method of survey work to make sure the Line of Sight BTS. The topographic surveyconsist of GPS survey and study map for determination of high of BTS antenna and the Line of Sight ofBTS can be made.